Endogenous AT1 Receptor–Protein Kinase C Activity in the Hypothalamus Augments Glutamatergic Input and Sympathetic Outflow in Hypertension - Ma, Huijie (J Physiol, 2019)
Increased synaptic N-methyl-D-aspartate receptor (NMDAR) activity in the hypothalamic paraventricular nucleus (PVN) plays a major role in elevated sympathetic output in hypertension. Although exogenous angiotensin II (AngII) can increase NMDAR activity in the PVN, whether endogenous AT1 receptor–protein kinase C (PKC) activity mediates the augmented NMDAR activity of PVN presympathetic neurons in hypertension is unclear. Here we show that blocking AT1 receptors with losartan or inhibiting PKC with chelerythrine significantly decreased the frequency of NMDAR-mediated miniature excitatory postsynaptic currents (mEPSCs) and the amplitude of puff NMDA currents of retrogradely labeled spinally projecting PVN neurons in spontaneously hypertensive rats (SHRs). Also, treatment with chelerythrine abrogated the potentiating effect of AngII on mEPSCs and puff NMDA currents of labeled PVN neurons in SHRs. In contrast, neither losartan nor chelerythrine had any effect on mEPSCs or puff NMDA currents in labeled PVN neurons in Wistar-Kyoto (WKY) rats. Furthermore, levels of AT1 receptor mRNA and PKC-mediated NMDAR phosphorylation in the PVN were significantly higher in SHRs than in WKY rats. In addition, microinjection of losartan or chelerythrine into the PVN substantially reduced blood pressure and renal sympathetic nerve discharges in SHRs but not in WKY rats. Chelerythrine blocked sympathoexcitatory responses to AngII microinjected into the PVN. Our findings suggest that endogenous AT1 receptor–PKC activity is essential for presynaptic and postsynaptic NMDAR hyperactivity of PVN presympathetic neurons and for the augmented sympathetic outflow in hypertension. This information advances our mechanistic understanding of the interplay between angiotensinergic and glutamatergic excitatory inputs in hypertension.